Ureteral fibroepithelial polyps in a pregnant woman: case report - Piovesan, Affonso Celso; Torricelli, Fábio César Miranda; Borges, Leonardo Lima; Chambô, José Luiz; Mesquita, José Luiz Borges de; Srougi, Miguel (São Paulo Medical Journal, 2009)
CONTEXT: Ureteral fibroepithelial polyps are rare benign nonepithelial tumors, and less than 200 cases have been reported in the literature. We report on a pregnant patient with ureteral fibroepithelial polyps that were successfully treated with laparotomy. CASE REPORT: A 23-year-old pregnant woman presented with a three-month history of intermittent lumbar pain of low intensity. Abdominal ultrasonography showed that she was 13 weeks pregnant and found severe left-side ureterohydronephrosis and a heterogeneous solid mass measuring 11 x 8 x 7 centimeters in the middle portion of the ureteral topography. The investigation was complemented with magnetic resonance imaging, which confirmed the previous findings. Nephroureterectomy was performed without complications. The specimen revealed three solid tumors in the ureter, of which the largest was around eight centimeters in length. The anatomopathological report confirmed that they were fibroepithelial tumors without malignant components.